Abendmahl digital empfangen?: Überlegungen angesichts aktueller Herausforderungen durch Pandemie(n) und Digitalisierung - Winter, Roman (Kerygma und Dogma, 2021)
The demand for an online Eucharist has recently resurfaced with significant pressure. However, a theological discussion about its practical feasibility and its implications is still in its beginnings. My contribution reflects from a systematic-theological perspective on the possibilities and obstacles of a digitally mediated Eucharist in a web conference. I focus on several problems that arise in the context of current digital practice. These problems concern the gift-nature of the sacrament, the physical sharing of the gifts, our real-presence in virtuality, and the individual chalice. This paper seeks to open up a possible spectrum of thoughts that rejects a simple yes or no to the digital Eucharist.